Analysis of Factors That Influence Indonesian GDP - Tri Dewi Kartika; Yusnida Yusnida (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This research aims to examine and determine the extent to which investment, labor force, and agricultural land area impact the Gross Domestic Product (GDP) of Indonesia between 2000 and 2020. Time series data was utilized as secondary data for this study. Multiple linear regression or Ordinary Least Square (OLS) was used as the analysis method. The findings indicate that investment has no significant impact on GDP, while labor force and agricultural land area have significant impacts on GDP in Indonesia. Therefore, it is recommended that the Indonesian government focus on creating more job opportunities to increase the workforce and expand agricultural land. Additionally, the government should consider reducing investments in Indonesia.